Sustainability analysis of fisheries and marine resource development in Indonesia’s blue economy framework - MUHAMMAD YUSUF; ANDI DYNA RIANA; RUSNENI RUSNENI; WIWIN ANGGRIANI SALAWALI; EDDIWAN EDDIWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Yusuf M, Riana AD, Rusneni, Salawali WA, Eddiwan. 2025. Sustainability analysis of fisheries and marine resource development in Indonesia’s blue economy framework. Biodiversitas 26: 3634-3646. Indonesia possesses vast and rich marine and fisheries resources. These resources play a critical role in ensuring national food security, driving economic growth, generating employment, and improving the welfare of coastal communities. However, the intensive utilization of marine resources must be accompanied by cautious and measurable management. Hence, evaluating the level of sustainability in fisheries and marine development is a vital and urgent necessity that cannot be overlooked. This study aims to analyze the level of sustainability in fisheries and marine development, as well as the factors that influence its sustainability. The research was conducted from August to November 2024. This study employed a quantitative approach using a survey research design. The data consisted of both primary and secondary sources, collected through survey questionnaires and desktop studies. The data analysis was carried out using the Multi-Dimensional Scaling – Rapid Appraisal for Fisheries (MDS RAPFISH) method. The research findings indicate that the sustainability index for the ecological dimension is 44.32 (unsustainable), the economic dimension is 37.75 (unsustainable), and the social dimension is 39.78 (unsustainable). Thus, the overall level of sustainability in fisheries and marine development in Indonesia is categorized as unsustainable, with an average index score of 40.62. The study also identified three key attributes that significantly influence the sustainability of fisheries and marine development in Indonesia: (i) the presence of key species (coral reefs, sea turtles, whales, tuna, sharks, and mangroves) with an Root Means Square (RMS) value of 4.88; (ii) investment in Indonesia’s maritime sector with an RMS value of 3.56; and (iii) the level of participation in decision-making processes with an RMS value of 3.91.